(untitled) (Orfeu, 2017)
This text briefly presents and discusses how the concept of teaching-learning among Guarani Mbya children was manifest in the way they, as collaborators in an ethnomusicological research work, taught their songs to the researchers. It also discusses cultural challenges encountered in the teaching and learning process among the guarani during the fieldwork. The paths taken in order to overcome these challenges bring to light the Guarani conception of childhood and, as a consequence, clarify how their children learn - and teach - reminding us of analyses regarding the ideal Deleuzian game.